2020
DOI: 10.1016/s2666-5247(20)30144-0
|View full text |Cite
|
Sign up to set email alerts
|

Viral presence and immunopathology in patients with lethal COVID-19: a prospective autopsy cohort study

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) targets multiple organs and causes severe coagulopathy. Histopathological organ changes might not only be attributable to a direct virus-induced effect, but also the immune response. The aims of this study were to assess the duration of viral presence, identify the extent of inflammatory response, and investigate the underlying cause of coagulopathy. Methods This prospective autopsy cohort study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
538
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(610 citation statements)
references
References 41 publications
(103 reference statements)
34
538
2
6
Order By: Relevance
“…Several recent tissue-based studies assessing CNS alterations in fatal COVID-19 have provided the first hints at histopathological changes occurring in COVID-19 such as hypoxia-related pathology including CNS infarction due to cerebral thromboembolism and signs of a CNS-intrinsic myeloid cell response [32][33][34][35][36][37][38] and/or have presented data on the presence of viral RNA in the CNS 4,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent tissue-based studies assessing CNS alterations in fatal COVID-19 have provided the first hints at histopathological changes occurring in COVID-19 such as hypoxia-related pathology including CNS infarction due to cerebral thromboembolism and signs of a CNS-intrinsic myeloid cell response [32][33][34][35][36][37][38] and/or have presented data on the presence of viral RNA in the CNS 4,39 .…”
Section: Discussionmentioning
confidence: 99%
“…A review of 28 papers by Maiese et al on a total of 341 cases showed alveolar damage with hyaline membrane formation and microthrombi in pulmonary vessels ( 43 ). In a recent autopsy study by Schurink et al in SARS-CoV-2, multiple organs had infected cells, especially in the lungs, but during the disease course these decreased ( 44 ). SARS-CoV-2-positive tissues also included heart, kidneys, and gastrointestinal tract.…”
Section: Clinical Findings: a Glance From The Specialistsmentioning
confidence: 99%
“…They conclude this suggests CD8+ T cells indeed contribute to viral clearance but may exert a degree of end organ damage ( 18 ). Schurink et al found either one of two types of T cell infiltration in all autopsies: a CD8+ infiltrate causing DAD, or a CD4+ interstitial infiltrate with exudative diffuse alveolar damage and bronchopneumonia ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the apparent downregulation of FOXP3 in CD4+ CD25+ T cells and their expression of FASL in Covid-19 patients ( 21 ), this could bode poorly for organs and immune-privileged sites. Following Covid-19 even canonically immune-privileged sites like the eye have inflammatory infiltrates ( 22 ) along with organs like the heart ( 19 ). Israelow et al observe hyperactivation of CD8+ cells and their infiltration into the lung in a murine model of Covid-19 ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation